Rho Kinase Regulates Schwann Cell Myelination and Formation of Associated Axonal Domains - Melendez-Vasquez, Carmen V. (J Neurosci, 2004)
The myelin sheath forms by the spiral wrapping of a glial membrane around an axon. The mechanisms involved are poorly understood but are likely to involve coordinated changes in the glial cell cytoskeleton. Because of its key role as a regulator of the cytoskeleton, we investigated the role of Rho kinase (ROCK), a major downstream effector of Rho, in Schwann cell morphology, differentiation, and myelination. Pharmacologic inhibition of ROCK activity results in loss of microvilli and stress fibers in Schwann cell cultures and strikingly aberrant myelination in Schwann cell-neuron cocultures; there was no effect on Schwann cell proliferation or differentiation. Treated Schwann cells branch aberrantly and form multiple, small, independent myelin segments along the length of axons, each with associated nodes and paranodes. This organization partially resembles myelin formed by oligodendrocytes rather than the single long myelin sheath characteristic of Schwann cells. ROCK regulates myosin light chain phosphorylation, which is robustly, but transiently, activated at the onset of myelination. These results support a key role of Rho through its effector ROCK in coordinating the movement of the glial membrane around the axon at the onset of myelination via regulation of myosin phosphorylation and actomyosin assembly. They also indicate that the molecular machinery that promotes the wrapping of the glial membrane sheath around the axon is distributed along the entire length of the internode.